Experimental study on thermal performances of heat sinks with cross-cut branched fins on horizontal cylinders under natural convection - Kim, Donghyuk; Kim, Dong Kwon (Journal of Mechanical Science and Technology, 2021)
In this study, experiments are conducted to measure the thermal resistances of heat sinks with cross-cut branched fins on horizontal cylinders. The experiments were conducted for several numbers of fin, heights of fins, and heat inputs. From the experimental data, the Nusselt number correlation for Rayleigh numbers of 190000–1000000, fin heights of 10–30 mm, and fin numbers of 9–36 is proposed. Using the suggested correlation, the fin thickness and fin number for maximizing the thermal performance are obtained. Finally, it is demonstrated that the optimal heat sink with cross-cut branched fins on a horizontal cylinder has 26 % lower thermal resistance than that of a conventional heat sink with plate fins.
Keywords: Fin numbers; Fin thickness; Heat input; Horizontal cylinders; Nusselt number correlation; Plate fins; Rayleigh number; Thermal Performance; Branched fins; Cross-cuts; Heat sinks; Horizontal cylinders; Natural convection; Nusselt number; Thermal resistances